2014
DOI: 10.1242/jeb.089441
|View full text |Cite
|
Sign up to set email alerts
|

Environmentally relevant stressors alter memory formation in the pond snailLymnaea

Abstract: Stress alters adaptive behaviours such as learning and memory. Stressors can either enhance or diminish learning, memory formation and/or memory recall. We focus attention here on how environmentally relevant stressors alter learning, memory and forgetting in the pond snail, Lymnaea stagnalis. Operant conditioning of aerial respiration causes associative learning that may lead to long-term memory (LTM) formation. However, individual ecologically relevant stressors, combinations of stressors, and bio-active sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
62
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 63 publications
(62 citation statements)
references
References 61 publications
0
62
0
Order By: Relevance
“…Snails are able to consolidate the associative learning into long-term memory (LTM) (Benjamin et al, 2000;Otsuka et al, 2013;Takahashi et al, 2013;Lukowiak et al, 2014;Sunada et al, 2014). Here, we look at the ability of Lymnaea to learn and remember for many days not to respond to a food substance that normally elicits a feeding response.…”
Section: Introductionmentioning
confidence: 99%
“…Snails are able to consolidate the associative learning into long-term memory (LTM) (Benjamin et al, 2000;Otsuka et al, 2013;Takahashi et al, 2013;Lukowiak et al, 2014;Sunada et al, 2014). Here, we look at the ability of Lymnaea to learn and remember for many days not to respond to a food substance that normally elicits a feeding response.…”
Section: Introductionmentioning
confidence: 99%
“…We defined stress here as a condition that significantly alters the physiological or psychological homeostasis of an organism (Lukowiak et al, 2014). The idea that exposure to a low-calcium environment, even for a short period of time (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…For example, detection of predator smells such as crayfish effluent (CE) enhanced both vigilance behaviours and LTM formation (Orr et al, 2007;Orr et al, 2009;Orr and Lukowiak, 2008); while crowding, low environmental calcium, and certain heavy metals (Zn and Cd) and H 2 S in pond water block LTM formation (Rosenegger et al, 2004;De Caigny and Lukowiak, 2008;Byzitter et al, 2012). A comprehensive summary of which ecologically relevant stressors significantly alter LTM formation can be found in two recent reviews (Lukowiak et al, 2014). It has also been shown that a flavonoid, epicatechin, found in dark chocolate, green tea and red wine (Kühnau, 1976;Matsuoka et al, 1995;Galliet al, 2002;Youdim et al, 2002) enhances LTM formation in Lymnaea (Fruson et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Memory formation is susceptible to alteration by environmental factors, such as stress and lifestyle choices [1]. One of these key lifestyle choices is diet.…”
mentioning
confidence: 99%
“…That is, the number of attempted pneumostome openings in the memory test session (MT) was not significantly less than the number in TS1. In the W-strain snails used here, this training procedure results in LTM formation when the training and testing sessions take place in pond water [1,18]. …”
mentioning
confidence: 99%